Study guides

☆☆

Q: What is y 2 over 5 y 3 over 3?

Write your answer...

Submit

Still have questions?

Continue Learning about Movies & Television

(y^2 + 3)(y^2 - 3y + 3)(y^2 + 3y + 3)

3

6x - 2y + 3xz - yz = (z + 2)(3x - y) 9x - 3y = 3(3x - y) (3x - y) over (3x - y) equals 1, so they can be canceled out. The simplified expression is (z + 2) over 3.

y=2x2+5. Plug in 0 for x, and you get y=2(0)^2 +5 =0+5=5. 5 is the minimum value for y.

(x)(x+y) ....or..... x2+xy

Related questions

y/9 - 2/5 = 1/3 => y = 6 3/5 or 6.6

Of course. These are straight lines. Y = 5/2 Y = 2/5

1+4=5

Sin(2*pi/6) = sin(pi/3) which, by definition, is 0.5 If you wish, you can calculate y/1! - y^3/3! + y^5/5! - y^7/7! + ... where y = pi/3.

Since we know the slope, m = 5/3, and the y-intercept 1/2, we arw able to write the equation of the line in the slope-intercept form, y = mx + b, so we have y = (5/3)x + 1/2.The standard form of the equation of the line is Ax + By = C.y = (5/3)x + 1/2y - y - 1/2 = (5/3)x - y + 1/2 - 1/2-1/2 = (5/3)x - y or(5/3)x - y = -1/2Thus, the standard form, Ax + By = C, of the equation of the line is (5/3)x - y = -1/2.

Slope = (y-5)/(3--6) = 1/3 y-5 = 1/3*9 y = 3+5 y = 8

5/(2y) + 3 + 6/y + 2 = 31. Bring all the unknown (all terms containing a letter, here Y) to one side and known to the other5/(2y) + 6/y = 3 + (-3) + (-2)2. multiply all by 2, to get rid of it where it stands next to the y(2*5)/(2y) + (2*6)/y = 2*(-2)3. Multiply all :)5/y + 12/y = -44. add all the terms with unknows17/y = -45. Therefore, y=17/(-4)and y=-4.25To check, just substitute y=-4.25 into the starting equation 5/(2y) + 3 + 6/y + 2 = 3Another method with the same result:5/2y + 3 + 6/y + 2 = 35/2y + 6/y = 3 -3 -25/2y + 6/y = -2Multiply all terms by 2y in ordes to eliminate the fractions:5 + 12 = -4y17 = -4yDivide both sides by -4 to find the value of y:y = -4.25Check by substituting the value of y into the original equation which will work out as: 3 = 3

5

y^2 X y^3 = y^(2 + 3) = y^5 You can only do this if the coefficient 'y' is the same for both terms. Remember y^2 = y X y y^3 = y X y X y Hence y^2 X y^3 = y X y X y X y X y = y^5 Similarly for division/subtraction y^3 / y^2 = y^(3 - 2 ) = y^1 = y The power of '1' is trivial and not normally shown. NB You CANNOT do z^2 X y^3 by adding the indices. z^2 X y^3 is (z^2)*(y^3)

2x-y=5, y=2x-5 4x+y=4, y=4-4x 2x-5=4-4x 6x=9 x=3/2 y= 2(3/2)-5 y=-2

the Y in the sentence X plus Y equals 5 is Y=3 or 2 if the X is 2 or 3

1. x + y = 22. y = 2x - 13Rewriting 2. as:3. 2x - y = 13Adding 1 & 3 gives:4. 3x = 15x = 5Substituting x = 5 into 1. gives:5 + y = 2y = 2 - 5y = -3Checking values by substituting x = 5 and y = -3 into 2 gives:-3 = (2 * 5) - 13-3 = 10 - 13-3 = -3Therefore x = 5 and y = -3.

People also asked